2019
DOI: 10.22342/jme.10.2.7307.203-214
|View full text |Cite
|
Sign up to set email alerts
|

Developing Mathematics Worksheet Using Futsal Context for School Literacy Movement

Abstract: School Literacy Movement, one of the government's efforts to optimize the ability of students in terms of literacy, needs support from every circle; one of them is from researches in the educational field. This research aims to develop reading texts in a futsal context that will be presented in students’ worksheet with valid and practical criteria that will have a potential effect in mathematics learning. This research is using the design research method with a development studies type that consists of three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The non-lesson mathematics books are still consistently similar with the results of interviews at stage 1 (literacy habituation), namely in the form of an encyclopaedia, math quick formulas, and a math dictionary. Meanwhile, the mathematical literacy texts expected at this stage are reading texts such as stories, scientific articles, other field material and various other reading contexts that students can imagine in which there are mathematical concepts such as literacy text entitled "Basic Techniques of Futsal Games" which was written by Effendi, Zulkardi, Putri, Yaniawati [9]. In this text, there found a straight-line concept while discussing the practice of passing and controlling a futsal ball.…”
Section: Questionnaire Results Of Mathematical Literacy Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-lesson mathematics books are still consistently similar with the results of interviews at stage 1 (literacy habituation), namely in the form of an encyclopaedia, math quick formulas, and a math dictionary. Meanwhile, the mathematical literacy texts expected at this stage are reading texts such as stories, scientific articles, other field material and various other reading contexts that students can imagine in which there are mathematical concepts such as literacy text entitled "Basic Techniques of Futsal Games" which was written by Effendi, Zulkardi, Putri, Yaniawati [9]. In this text, there found a straight-line concept while discussing the practice of passing and controlling a futsal ball.…”
Section: Questionnaire Results Of Mathematical Literacy Developmentmentioning
confidence: 99%
“…The notion of development is in line with the objectives of school literacy movement at the development stage by which students are expected to be able to discover how the books or reading sources they read in their surroundings are interrelated which shows involvement of the mind, productive activities both orally and in writing where the reading text is chosen by students voluntarily to foster enthusiasm to participate in the activities [9], [10]. Mathematics reading materials can also be provided by the teachers which require them to possess good mathematical literacy conceptions.…”
Section: Introductionmentioning
confidence: 85%
“…Telah banyak penelitian pengembangan (Research and Development) yang menghasilkan produk-produk bahan ajar yang berkualitas untuk pembelajaran. Beberapa penelitian pengembangan menghasilkan bahan ajar soal tipe PISA untuk tingkat SMP (Nizar et al, 2018;Noviarsyh Dasaprawira et al, 2019;Oktiningrum et al, 2016), , scientific bilingual worksheet untuk mahasiswa (Sagita et al, 2018), multimedia flipbook untuk SD kelas 6 (Andini et al, 2018), produk bahan ajar teks bacaan dengan konteks futsal untuk SMP (Effendi et al, 2019), soal open-ended untuk SMP (Kurniawan et al, 2018) dan masih banyak lagi. Keseluruhan penelitian hasil pengembangan tersebut menunjukkan bahwa produk bahan ajar yang dibuat bersifat praktis untuk digunakan dan berefek baik dalam pembelajaran.…”
Section: Pendahuluan *unclassified
“…Furthermore, to support literacy activities for elementary school students, the Ministry of Education and Culture designed the School Literacy Movement (GLS) program based on Permendikbud Number 23 of 2015 concerning the Growth of Character and Character (Ermerawati, 2019). The purpose of forming GLS, according to previous study is that students have a habit of reading and writing activities so that they become literate students and lifelong learning (Effendi et al, 2019). Then, the opinion of other study revealed that the application of literacy for elementary school students, namely being able to realize literate students, being able to bring students to face challenges in the future and facilitating students to obtain information and solution to the problem (Marmoah & Poerwanti, Suharno, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of relevant research conducted argues that the implementation of GLS in a structured and systematic manner has a positive impact on the growth of literacy achievements for students (Ermerawati, 2019;Pratiwi et al, 2022;Purwaningrum et al, 2021;Ramandanu, 2019;Widodo & Umar, 2021). Based on this relevant research, three components can be used in developing literacy programs in schools: good management practices, facilitating students to build a culture of literacy and integrating 21st-century skills in learning (Effendi et al, 2019;Nuryana et al, 2020;Wahab & Amaliyah, 2021). GLS implementation according to previous study is three stages: the habituation stage, the development stage, and the learning stage (Yunianika & Suratinah, 2019).…”
Section: Introductionmentioning
confidence: 99%